Heat Transfer: Volume 3 2008
DOI: 10.1115/ht2008-56318
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Flow Structures in Aircraft Wing Compartments

Abstract: The use of composite material in modern commercial aircraft has increased significantly in recent years. The very low conductivity relative to Aluminium of composite materials means that the thermal environment experienced in an aircraft, during flight and on the apron, are significantly altered. The heat transfer mechanism is complex: natural and mixed convection flows established in compartments. This paper presents the thermally induced flow structures under representative conditions for a rectangular cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The present scenario does not incorporate stringers. Newport et al [39] demonstrated experimentally and numerically that stringers result in a conductive layer that extends from the base of the stringer to its tip, effectively reducing the aspect ratio of the compartment.…”
Section: Experimental Model Of a Wingboxmentioning
confidence: 99%
“…The present scenario does not incorporate stringers. Newport et al [39] demonstrated experimentally and numerically that stringers result in a conductive layer that extends from the base of the stringer to its tip, effectively reducing the aspect ratio of the compartment.…”
Section: Experimental Model Of a Wingboxmentioning
confidence: 99%